Differences in Nutritional Status and Quality of Life in Hemodialysis Patients Compared to CAPD - Kosasih, Angelia; Samsu, Nur; Rifa'i, Achmad (Universitas Brawijaya, 2024)
Background: Patients with chronic kidney disease who undergo hemodialysis and CAPD (Continous Ambulatory Peritoneal Dialysis) modalities often experience disturbances in nutritional status and quality of life. The condition is affected by the chosen modalities and duration. Aim: This study assesses the differences in nutritional status and quality of life in individuals undergoing hemodialysis therapy with a duration of 4-hour, hemodialysis with a duration of 5-hour, and CAPD in order to determine the best modalities for patients with chronic kidney disease. Methods: Data were collected with cross-sectional from patients with chronic kidney disease at the hemodialysis polyclinic at RSUD dr. Saiful Anwar Malang, Panti Nirmala Hospital Malang, Wava Husada Kepanjen Hospital, and the CAPD polyclinic at RSUD dr. Saiful Anwar Malang. Classified into CAPD group, 4-hour hemodialysis group, and 5-hour hemodialysis group. Assessment with a questionnaire consisting of the patient’s baseline characteristics, subjective global assessment (SGA), and SF-36 are used to assess and analyze differences in nutritional status and quality of life of patients with chronic kidney disease against the selected dialysis modality. Results: The physical health of the 5-hour hemodialysis group showed significant results compared to the 4-hour hemodialysis and CAPD (p <0.05). Mental health in the 5-hour hemodialysis procedure showed significant results compared to the 4-hour hemodialysis and CAPD (p <0.05). The nutritional status of 5-hour of hemodialysis was better than 4-hour of hemodialysis and CAPD (p<0.05). Conclusion: Hemodialysis with a duration of 5-hour has a better nutritional status and quality of life compared to a duration of 4-hour or CAPD.